1973
DOI: 10.1037/h0035657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of work sample test upon self-selection and turnover of job applicants.

Abstract: Hypothesized that job applicants who were administered a pre-employment work sample test and who, consequently, had a more accurate expectancy about task requirements would have a higher job refusal rate and a lower voluntary turnover rate than applicants not administered the work sample test. Ss were 67 white and 93 black female applicants for the job of sewing machine operator. Some support for the hypotheses was found for white Ss but not for black Ss. Racial differences are explained in terms of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 5 publications
0
25
1
Order By: Relevance
“…Research in the psychology literature mostly during the 1970s suggested that more information, positive as well as negative, prior to the start of an employment relationship is associated with lower turnover (Gannon 1971;Farr, O'Leary and Bartlett 1973;Ilgen and Seely 1974;Wanous 1973Wanous , 1975Mencken and Winfield 1998). More recent empirical work by labor economists has generally supported the hypothesis that informal recruiting methods are associated with higher productivity and longer average tenure than other methods (Reid 1972;Datcher 1983;Barron, Bishop and Hollenbeck 1983;Holzer 1987;Roper 1988;Simon and Warner 1992;van Ours and Ridder 1992;Bishop 1993;Gorter, Nijkamp and Rietveld 1996;DeVaro and Fields 2004).…”
Section: Previous Literaturementioning
confidence: 99%
“…Research in the psychology literature mostly during the 1970s suggested that more information, positive as well as negative, prior to the start of an employment relationship is associated with lower turnover (Gannon 1971;Farr, O'Leary and Bartlett 1973;Ilgen and Seely 1974;Wanous 1973Wanous , 1975Mencken and Winfield 1998). More recent empirical work by labor economists has generally supported the hypothesis that informal recruiting methods are associated with higher productivity and longer average tenure than other methods (Reid 1972;Datcher 1983;Barron, Bishop and Hollenbeck 1983;Holzer 1987;Roper 1988;Simon and Warner 1992;van Ours and Ridder 1992;Bishop 1993;Gorter, Nijkamp and Rietveld 1996;DeVaro and Fields 2004).…”
Section: Previous Literaturementioning
confidence: 99%
“…When an individual's expectations are not substantially met, their propensity to withdraw increases (Porter & Steers, 1973). Empirical research however has reported no statistically significant relationship between met expectations and turnover (Dunnette, Avery, & Banas, 1973;Farr, O'Leary, & Bartlett, 1973). More importantly, no research has examined the relationship between met expectations and satisfaction.…”
Section: Relationship Between Goal Change and Endogenous Variablesmentioning
confidence: 93%
“…Two studies have examined the relationship between met expectations and turnover, but neither found a significant relationship (Dunnette et al , 1973;Farr et al , 1973). It is posited that there is a relationship in a positive direction between goal change and turnover.…”
Section: Relationship Between Goal Change and Withdrawal Behaviormentioning
confidence: 97%
“…1) reducing response bias and faking compared to self reports of attitudes, heliefs and interests (Wernimont and Campbell, 1968), 2) minimizing the disadvantages for individuals who have limited education and/or low level verbal skills, and 3) providing the examinees with more realistic expectations about the job (Pruitt, 1970;O'Leary, 1973;and Farr, O'Leary and Bartlett, 1973). The latter of these advantages is of significant interest in light of research which has shown that realistic job previews can decrease the likelihood of subsequent voluntary resignations (Ilgen and Seeley, 1974).…”
Section: )mentioning
confidence: 99%